Classroom Silence and its Meaning in English Language Learning Contexts - Suardi Suardi (PT FORMOSA CENDEKIA GLOBAL, 2026)
Classroom silence is a pervasive phenomenon in English as a Foreign Language (EFL) learning contexts, yet it remains insufficiently understood within mainstream language pedagogy. Classroom silence has long been perceived as a sign of disengagement or lack of competence in English language learning contexts. However, recent perspectives in applied linguistics suggest that silence may carry complex pedagogical, cognitive, and sociocultural meanings. This study aims to explore the forms, functions, and underlying meanings of classroom silence in English as a Foreign Language (EFL) learning environments. Employing a qualitative research design with a case study approach, data were collected through classroom observations, in-depth interviews with students and teachers, and reflective field notes.